1995
DOI: 10.1111/j.1476-5381.1995.tb16345.x
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐mediated inhibition of the anaphylactic response in the guinea‐pig trachea

Abstract: In sensitized guinea‐pigs, the effects of γ‐aminobutyric acid (GABA) and GABAmimetic drugs have been investigated on tracheal segments contracted by cumulative application of an allergen (ovoalbumin, OA) and on serosal mast cells. The same drugs have also been tested on activation of alveolar macrophages isolated from unsensitized guinea‐pigs. Superfusion with GABA (1–1000 μM) reduced the contraction intensity of tracheal strips. The effect of GABA (100 μM) was not affected by the carrier blockers, nipecotic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Acid evoked cough may be mast cell dependent, and mast cell activation may trigger or at least modulate subsequently evoked cough [51,52]. GABA B receptor agonists can attenuate allergen-induced inflammation, perhaps through effects on mast cell activation [53,54]. GABA B receptors on non-neural airway cells has also been documented, including airway smooth muscle and epithelium [55,56], and we have described a transduction pathway dependent upon activation of chemosensory epithelial cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Acid evoked cough may be mast cell dependent, and mast cell activation may trigger or at least modulate subsequently evoked cough [51,52]. GABA B receptor agonists can attenuate allergen-induced inflammation, perhaps through effects on mast cell activation [53,54]. GABA B receptors on non-neural airway cells has also been documented, including airway smooth muscle and epithelium [55,56], and we have described a transduction pathway dependent upon activation of chemosensory epithelial cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…inhibition of release of substance P from capsaicin-sensitive neurones in the rat trachea (578) and of acetylcholine secretion from cholinergic nerves in the lung and in the colon (576578). GABA itself has been shown to inhibit the anaphylactic response in guinea-pig trachea (579). It has been found that there are different subtypes of GABA B receptors in the central nervous system which differ in their sensitivity to taurine as an agonist (while all of them, of course, are sensitive to GABA).…”
Section: Antiinflammatory Effects Of Taurinementioning
confidence: 99%
“…1 The parasympathetic nervous system plays a dominant role in the control and regulation of the respiratory system in humans and in animals. 4,[8][9][10][11][12][13] In the airways, GABA has been implicated in the regulation of tracheal smooth muscle tone through both central and peripheral mechanisms. 2 It is known that GABA is a major inhibitory neurotransmitter and neuromodulator of the central and peripheral nervous systems.…”
Section: Introductionmentioning
confidence: 99%